PENGARUH MANAJEMEN LABA DAN GOOD CORPORATE GOVERNANCE TERHADAP TAX ACOIDANCE PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI (BURSA EFEK INDONESIA) TAHUN 2016-2019 - Selvia Sandi, (2022)
This study aims to determine the effect of earnings management and good corporate governance on tax avoidance in consumer goods companies listed on the Indonesia Stock Exchange in the 2016-2019 period over the year. This research is a type of quantitative research, that uses secondary data in the form of financial statements or company annual reports. The sample in this study were 61 consumer goods companies. The data analysis technique in this study used a regression model selection test, classical assumption test, panel data regression, and partial hypothesis testing (t test). Based on the results of data analysis, it can be concluded that (1) real earning management via abnormal cash flow has a significant positive effect on tax avoidance, (2) real earning management via abnormal discretionary expense has no significant positive effect on tax, (3), real earning management via abnormal production discretionary cost has a significant positive affect on tax avoidance, (4) women on board of directors has no significant negative effect on tax avoidance, (5) independen commissioners has no significant negative on tax avoidance and the control variables are (6) leverage has no significant effect on tax avoidance, and (6) firm size has no significant effect on tax avoidance. Keywords: Real Earning Management, Women On Board Of Directors, Independen Commissioners, Leverage, Company Size, And Tax Avoidance